THE USE OF ALTERNATIVE WRITING ASSESSMENT FOR SENIOR HIGH STUDENTS - Muroqobah, Musfi; Femilia, Praptika Septi (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2025)
Assessment plays a crucial role for teachers in monitoring students' performance and evaluating the students skills. Alternative writing assessment aims to foster a deeper understanding of students' capabilities in expressing themselves through writing. The research was conducted in the 11th-grade students at SMAN Umbulsari, utilizing a descriptive qualitative design as the research approach. Data collection methods included observations, interviews, and document reviews. To ensure data validity, triangulation of sources and techniques was employed. From the data revealed several findings for the forms are; journals, observations, self-peer assessment. The procedures were: a) Journal, teacher gave guidlines, designed scoring rubric, calculating the score. b) Self-peer assessment, students exchange their work with their partners, then correct each other, gave correct and incorrect assessments. c)Observation, students mention the difficulties of their writing, then teacher gave feedback. Strengths from assessment alternative writing are: students could wrote well according to the lesson theme, easily created outlines based on the lesson theme, also easily discussion with partners to improves understanding. Meanwhile, the weakness is the students needed sufficient time to do their writing tasks. It can provide some additional information about alternative writing assessments, and provide an overview for their use during the learning process.